Pengaruh pendidikan mitigasi bencana tanah longsor terhadap kesiapsiagaan masyarakat didesa melung kecamatan kedungbanteng kabupaten banyumas - Rachmi Ariyani; Endiyono - Endiyono (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Understand Effect of Education Mitigation of Disasters Land landslide against Preparedness Society in Rural Melung District of Kedungbanteng Regency of Banyumas. Methods: This study uses quantitative methods with quasy experimental designs through the one group pretest-posttest design approach. Test were used in research this is a test paired sample t test with a number of 50 respondents were taken by proposive sampling. Results: Result statistical test p-value = 0.0001 ( p-value < 0.05) which means that there are significant landslide disaster mitigation education to the knowledge society in the village of the District Melung Kedungbanteng Banyumas Regency. This influence is indicated by an increase of 5,640 points from the score before training of 6,140. The difference of 5,640 is statistically significant.Conclusion: The preparedness of the village community in melung is included in the category of being ready to face the possibility of a landslide disaster, before the training knowledge of the people of 6,15 but after the knowledge of the rise of 11,78.Keywords: Mitigation disasters soil landslides, Preparednes, Education.